Synthetic Approaches to Halogen Bonded Ternary Cocrystals. Issue 23 (29th April 2021) - Jain, Harsh; Sutradhar, Dipankar; Roy, Sourav; Desiraju, Gautam R.
Abstract: Higher cocrystal synthesis depends acutely on a knowledge of supramolecular synthons. We report three synthetic approaches towards ternary halogen bonded cocrystals that illustrate specificity and generality. Electrophilicity/nucleophilicity differences are needed among alternative sites of halogen bond formation. The two halogen bonds A⋅⋅⋅B and B⋅⋅⋅C in a halogen bonded ternary cocrystal ABC need to be of different strength. Interaction mimicry of hydrogen bonds by halogen bonds is a viable approach towards ternaries as illustrated with the pyrene structure. Finally, the crystal engineer should well be able to anticipate halogen bonds that are stronger than hydrogen bonds. Abstract : Halogen bonded ternary cocrystals were synthesized by employing three different approaches. The possible reasons for the formation of these cocrystals have been proposed based on a detailed crystal packing analysis and computational results.